2004
DOI: 10.1164/rccm.200306-767oc
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Function in Obstructive Sleep Apnea and Response to Treatment

Abstract: Impaired endothelium-dependent vascular relaxation is a prognostic marker of atherosclerosis and cardiovascular disease. We evaluated endothelium-dependent flow-mediated dilation (FMD) and endothelium-independent nitroglycerin (NTG)-induced dilation of the brachial artery with Doppler ultrasound in 28 men with obstructive sleep apnea (OSA) and 12 men without OSA. Subjects with OSA (apnea-hypopnea index; mean +/- SD, 46.0 +/- 14.5) had lower FMD compared with subjects without OSA (5.3 +/- 1.7% vs. 8.3 +/- 1.0%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
379
4
21

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 539 publications
(421 citation statements)
references
References 51 publications
17
379
4
21
Order By: Relevance
“…Furthermore, there is evidence that treatment of OSA with nasal CPAP therapy improves endothelial function and reduces the risk for fatal and nonfatal cardiovascular events. 31 The possibility of OSA causing or accelerating atherosclerosis has been supported by data from several studies. 32 -35 Obstructive sleep apnea being an independent risk factor for atherosclerosis is further supported by a randomized controlled trial in which intervention by CPAP resulted in significant reduction in carotid intima-media thickness.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, there is evidence that treatment of OSA with nasal CPAP therapy improves endothelial function and reduces the risk for fatal and nonfatal cardiovascular events. 31 The possibility of OSA causing or accelerating atherosclerosis has been supported by data from several studies. 32 -35 Obstructive sleep apnea being an independent risk factor for atherosclerosis is further supported by a randomized controlled trial in which intervention by CPAP resulted in significant reduction in carotid intima-media thickness.…”
Section: Discussionmentioning
confidence: 95%
“…Several experimental and clinical studies have shown that nocturnal hypopnea induces increases in blood pressure levels 6,19 and the progression of arterial stiffness. 18,19 Endothelial dysfunction 4,[20][21][22] and disturbances of sympathetic activity 5,23 are recognized clinical features in OSA patients that increase vascular tone and accelerate the progression of arterial stiffness. 7 Chronic intermittent hypoxia causes dyslipidaemia and initiates the development of atherosclerosis, both of which contribute to arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Atherosclerosis is a progressive disease that is also a pivotal risk factor for these cardiovascular disorders. OSA induces systemic HT, inflammation, 3 endothelial dysfunction 4 and disturbances in sympathetic activity, 5 all of which are known to accelerate the development of atherosclerosis. It has been shown that continuous positive airway pressure (CPAP) treatment improves these risk factors for atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brachial artery FMD: Patients were studied in the fasting state and all vasoactive medications were withheld for at least 12 h before the study. As previously described, 10,11 longitudinal scans of the brachial artery were obtained at rest, and then FMD was induced by inflation of a pneumatic tourniquet placed on the forearm to a pressure of 250 mm Hg for 5 min. The cuff was then released and serial imaging of the brachial artery was recorded for 5 min.…”
Section: Ultrasound Examinationmentioning
confidence: 99%